The Apionidae (Coleoptera: Curculionoidea) of New Caledonia. Genera Archellerenius gen. nov. and Hellerenius Wanat - Wanat, Marek (Zootaxa, 2013)
The New Caledonian endemic weevil genus Hellerenius is revised, with three new species described: H. monteithi, H. plumipes, and H. tibialis. A new genus Archellerenius is proposed for Archellerenius giustoi n. sp. Diagnoses, a key and distribution maps are provided for all species. Association of Hellerenius with the plant genus Hedycarya (Monimiaceae) is confirmed.